2001
DOI: 10.1038/35065604
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking the M3 muscarinic acetylcholine receptor are hypophagic and lean

Abstract: Members of the muscarinic acetylcholine receptor family (M1-M5) have central roles in the regulation of many fundamental physiological functions. Identifying the specific receptor subtype(s) that mediate the diverse muscarinic actions of acetylcholine is of considerable therapeutic interest, but has proved difficult primarily because of a lack of subtype-selective ligands. Here we show that mice deficient in the M3 muscarinic receptor (M3R-/- mice) display a significant decrease in food intake, reduced body we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
308
2
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(327 citation statements)
references
References 25 publications
15
308
2
2
Order By: Relevance
“…66,71,72 Notably, a subset of MCH neurons coexpresses the M3 muscarinic acetylcholine receptor (M3Ach-R), and M3Ach-R À/À mice are hypophagic despite extremely low levels of serum leptin. 201 MCH accelerates feeding in M3Ach-R À/À mice when administered centrally, whereas an AgRP analogue does not. This study indicates that M3Ach-R-mediated acetylcholine signaling at a site downstream of the leptin/melanocortin system and upstream of the MCH system is critical in facilitating food intake.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…66,71,72 Notably, a subset of MCH neurons coexpresses the M3 muscarinic acetylcholine receptor (M3Ach-R), and M3Ach-R À/À mice are hypophagic despite extremely low levels of serum leptin. 201 MCH accelerates feeding in M3Ach-R À/À mice when administered centrally, whereas an AgRP analogue does not. This study indicates that M3Ach-R-mediated acetylcholine signaling at a site downstream of the leptin/melanocortin system and upstream of the MCH system is critical in facilitating food intake.…”
mentioning
confidence: 94%
“…This study indicates that M3Ach-R-mediated acetylcholine signaling at a site downstream of the leptin/melanocortin system and upstream of the MCH system is critical in facilitating food intake. 201 Anticholinergic agents are occasionally used to alleviate extrapyramidal adverse effects by neuroleptics. It is significant to examine if and how anticholinergic medication in psychiatric practice influences body weight homeostasis.…”
mentioning
confidence: 99%
“…Typical and atypical antipsychotic drugs have a complex pharmacology, interacting with a number of serotonergic (eg 5-HT 1A , 5-HT 2A , 5-HT 2C , 5-HT 6 and 5-HT 7 (Roth et al, 1992(Roth et al, , 1994(Roth et al, , 1998, dopaminergic (eg D 2 , D 3 , and D 4 (Seeman and Lee, 1975;Seeman et al, 1997;Van Tol et al, 1991), histaminergic (eg H 1 (Peroutka et al, 1980) and H 4 (Nguyen et al, 2001)), adrenergic, and muscarinic acetylcholine receptors (Bolden et al, 1992;Zeng et al, 1997). In mice, targeted deletion of some of these receptors can have effects on body weight; for example, 5-HT 2C receptor knockout mice are obese (Tecott et al, 1995), whereas m3-muscarinic receptor knockout mice are lean (Yamada et al, 2001). The results with 5-HT 2C receptor and m3-muscarinic receptor knockout mice imply that the interactions of antipsychotic drugs with these receptors may be responsible for weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…Antisense 14,15 and gene targeting technologies have emerged as powerful new tools in identifying the receptor subtypes involved in various muscarinic cholinergic functions. [16][17][18][19][20][21] Although pharmacological, neuroanatomical and clinical studies have suggested an important role of muscarinic receptors in synaptic plasticity and memory, the functions of the individual muscarinic receptor subtypes remain unclear. In this study, we have used M2 and M4 receptor single knockout (KO) as well as M2/M4 receptor double KO mice to investigate the functional importance of M2 and M4 receptors in the regulation of acetylcholine release in the hippocampus and in cognitive processes.…”
Section: Introductionmentioning
confidence: 99%